The influence of urban street-side greenery on people’s visual preference - Ernawati, J (ASCEE, 2022)
This study purposed to identify urban street-side greenery’s effect on people's preferences towards streets in Malang town, Indonesia. Nine samples of streets were randomly selected based on greenery conditions and street typologies. Thirty participants for each street systematically selected came to a total of 270 respondents. The research instrument was a questionnaire with photos of the nine streets as stimuli to explore people's preferences towards street-side greenery based on six street greenery variables and two street conditions using multiple rating scales. The data analyses employed a descriptive statistic to determine people's preferences and multiple regression analysis to identify street greenery attributes that influence people's visual preference of the street. The results show that all street greenery attributes significantly influence people's preferences (p .05). As a whole, street-side greenery attributes, i.e., plant height, green street median, vegetation arrangement, the distance between trees, tree and vegetation species, and the number of trees, determine around 17.2% of urban street visual preferences. Among those street greenery qualities, the number of trees, vegetation arrangement, and green street median existence have the most influence on people's visual preferences. However, other than street greenery attributes, the street conditions (i.e., street width and the sidewalk width) significantly contribute to people's preference. It accounts for around 49.4% of the visual preference of the street.